Kinerja Perawat di Rumah Sakit Ibnu Sina Kota Makassar - Sherly Rudianti Batter; Rika Kurnia Kandacong (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The quality of service in hospitals cannot be separated from the problem of nurse performance. This is related to the presence of nurses who are on duty 24 hours a day to serve patients. Therefore, hospitals must have nurses who perform well who will support hospital performance so that customer or patient satisfaction is achieved. Nurse performance makes a major contribution in influencing patient satisfaction, considering that nurses are medical personnel who are in direct contact with patients. The aim of this research is to determine the performance of nurses at Ibnu Sina Hospital, Makassar City Â based on work stress, work relationships and work discipline. This research is a descriptive study with sampling using the total sampling method on 162 nurses. The results of the study showed that the performance of nurses in carrying out maintenance tasks obtained quite good performance (100%), the work stress of nurses obtained that nurses were quite stressed (48%), the work relationship in obtaining quite good results (100%), work discipline was included in the category of sufficient work discipline ( 100%). The conclusion of this research is that the performance of nurses at Ibnu Sina Hospital, Makassar City was in the quite good category.